An experimental and numerical study on tactile neuroimaging: A novel minimally invasive technique for intraoperative brain imaging. Issue 2 (30th January 2018) - Sadeghi‐Goughari, Moslem; Qian, Yanjun; Jeon, Soo; Sadeghi, Sohrab; Kwon, Hyock‐Ju
Abstract: Background: The success of tumour neurosurgery is highly dependent on the ability to accurately localize the operative target, which may shift during the operation. Performing intraoperative brain imaging is crucial in minimally invasive neurosurgery to detect the effect of brain shift on the tumour's location, and to maximize the efficiency of tumour resection. Method: The major objective of this research is to introduce tactile neuroimaging as a novel minimally invasive technique for intraoperative brain imaging. To investigate the feasibility of the proposed method, an experimental and numerical study was first performed on silicone phantoms mimicking the brain tissue with a tumour. Then the study was extended to a clinical model with the meningioma tumour. Results: The stress distribution on the brain surface has high potential to intraoperatively localize the tumour. Conclusion: Results suggest that tactile neuroimaging can be used to provide non‐invasive and real‐time intraoperative data on a tumour's features.